Meningkatkan Literasi Menulis Siswa Pelajaran Bahasa Indonesia Melalui Pendekatan Keterampilan Proses Kelas VI SDN 3 Sekarteja Tahun Pelajaran 2021/2022 - Muh Roni Hidayatullah; Samsul Rizal; Ahmad Fatoni (Universitas Wijaya Kusuma Surabaya, 2022)
This study aims to: (1) Improve the achievement of learning Indonesian, especially in class VI SDN 3 Sekarteja (2) Knowing the improvement of writing skills in learning Indonesian. This research is a classroom action research. The data in this study were sourced from the sixth grade students of SDN 3 Sekarteja. The method used in this research is the Process Skills Approach. The results of this study are (1) the students' learning achievement in Indonesian increases, (2) the process literacy skills approach can be used as a means to improve students' poetry writing skills effectively. Keywords: literacy, learning achievement, writing poetry, students